Introducing Ebola (EVD): An Unnecessary Surprise - Bindenagel Šehović, Annamarie (Coordinating Global Health Policy Responses, 2017)
Chapter 4 tackles the Ebola (Ebola Virus Disease, EVD) pandemic of 2014/2015. It notes that coming in the wake of the ongoing HIV pandemic, the rights of those infected with Ebola to be identified and treated were largely uncontested. The questions of who would be treated, by whom, with what, remained however extremely contentious. The international response to the pandemic also saw, for the first time, not only non-state actors involved in mediating and mitigating a health crisis, but also military intervention. This chapter lays out both the uses and the dilemmas of military response. It explores the impact of these interventions in this Ebola pandemic, with a view towards possible future military deployments against health threats, and offers an initial analysis of the consequences thereof on the relationship between individual and state rights and responsibilities.